Public Opinion of Citizens of Modern Russia on Police Activities: Theoretical-Legal and Sociological Aspects - Vladimir Valentinovich Kozhevnikov (Britain International for Academic Research (BIAR-Publisher), 2024)
This article examines a number of general theoretical issues concerning the concept of legal consciousness, the subject of its reflection and functions. Particular attention is focused on the evaluative function of legal consciousness, with the help of which the activities of law enforcement agencies in general and the police in particular are assessed. The theoretical position on the existence of a correlation between a particular attitude toward the police and the level of legal activity of citizens is substantiated by the results of sociological research.